Industri Media Massa Lokal dalam Tinjauan Manajemen Media Ideal - Ida Ri'aeni; Widia Sulistiana (JIKE: Jurnal Ilmu Komunikasi Efek, 2018)
Abstract The Growth and development of local media in Indonesia, seems still far behind compared with the growth and development of national media. The mass media industry is a creative industry that will continue to grow as the human need for knowledge, art and entertainment. The communication industry, especially the media, involves three important institutions, namely research institutes, advertising agencies / consultants, and media institutions. Media management is a study of how the management of media with the principles and all the management process is done, both to the media as an industry that is commercial and social. Idealism as a media institution and commercialism as a business institution becomes a complementary part of media management. Media management changes with the changing nature of the media. In Cirebon, growing dozens of print media, online / cyber, radio and local telegram. The focus of this study is how to look at the development of local mass media as a creative industry in terms of media regulation. Keyword: creative industry, media management, local mass media, idealism and commercialism. Abstrak